2014
DOI: 10.1093/trstmh/tru010
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hepatitis B and liver schistosomiasis: a deleterious association

Abstract: The association between replicative CHB and schistosomal PF can be a risk factor for more severe liver disease, which can result in deleterious outcomes for patients from endemic areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 36 publications
1
9
1
Order By: Relevance
“…This contrasts with recent investigations as those of Andrade et al [23] from Brazil. In their study, they too compare patients with chronic HBV infection with and without schistosomiasis, and do find differences in AST levels, platelet count, and cirrhosis prevalence.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…This contrasts with recent investigations as those of Andrade et al [23] from Brazil. In their study, they too compare patients with chronic HBV infection with and without schistosomiasis, and do find differences in AST levels, platelet count, and cirrhosis prevalence.…”
Section: Discussioncontrasting
confidence: 94%
“…Another relevant fact is that the studies performed in endemic areas, mainly Brazil and Egypt [10][11][12][13][14]23], include a high proportion of cirrhotic patients (from 31.5 to 48 %). On the contrary, in our series there were very few cirrhotic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, most published studies have found no association between schistosomiasis and worsening of HBV infection [ 53 ]. In contrast, other studies described a poor prognosis of HBV when associated with hepatosplenic schistosomiasis [ 17 , 24 , 54 ]. Interestingly HBV vaccines (both 1st and 2nd generation) can mount an immune response in schistosomiasis patients; however, reduced responses to vaccination were seen in hepatosplenic schistosomiasis [ 37 , 55 , 56 ].…”
Section: Introductionmentioning
confidence: 87%
“…Also, S . mansoni and hepatitis B co-infection has been associated with more severe liver disease [19]. …”
Section: Introductionmentioning
confidence: 99%